Framed: COP17 on South African television - Meiring, Rouxnette (Centre for Film and Media Studies, 2016)
The media have a critical role to play in informing and changing public opinion on climate change, "the defining human development issue of our generation" (United Nations Development Programme for Human Development Report, 2008, 1). Developing countries are most likely to suffer the worst effects of climate change, yet few studies exist on climate change communication in the media in developing countries and in particular in Africa. Studies on climate change communication in the media focus mostly on the print media and on developed countries, yet in Africa, more people consume their news through television or radio. So far, no study has examined television news reports of a United Nations Conference of the Parties in Africa. This study examines the way four South African television news stations (three public and one private) framed climate change news over six weeks: two weeks before, during and after the 17th United Nations Conferences of the Parties in Durban (COP17) South Africa, 2011/11/07 – 2012/01/07. Coding words were used to identify climate change stories in the main newscasts on SABC 1, 2, 3 and e.tv each day. These were transcribed and in the cases of SABC1 and 2 broadcasts translated from three indigenous languages (Afrikaans, isiXhosa and isiZulu) into English. A quantitative, descriptive statistical analysis looked at the occurrence of four primary frames in these climate change stories, using binary coding questions to identify each frame. The results in the binary coding sheets were analysed by using spreadsheets. The coding questions were also used to identify and explore secondary and additional frames, which were then illustrated in graphs. Differences in framing between public and private television were also illustrated in graphs (for example local versus foreign stories, time devoted to stories, depth of stories and occurrence of climate change stories with a human angle). Secondly, a qualitative inductive analysis of text and visual material looked at links between frames (for example the link between extreme weather conditions and human action using cause and impact visuals, as well as the link between news image and source – the framing of the politician, the activist and the scientist.) This section also looked at emotionally anchoring images of hope and guilt and the role of banners, posters and maps in climate change stories on television. Though other studies claim that coverage of the summit was "almost invisible" (Finlay 2012, 16) this study shows very high coverage on especially SABC 1 (isiXhosa and isiZulu). The following hypotheses were confirmed: the political/economic frame will dominate on all stations during COP17 but the ecological frame will be highest on at least some stations in the weeks after COP17. The ethics frame will be dominated by the secondary "Inequality/Justice" frame while the "Religion" frame will be of minimal importance. When activists set the agenda, the motivational frame will hardly feature. Climate change scepticism will receive little attention on South African television. Local (South African and African) stories will be more prominent on public television than on private television.